1992
DOI: 10.1007/bf02102631
|View full text |Cite
|
Sign up to set email alerts
|

The structure of naked singularity in self-similar gravitational collapse

Abstract: We study the structure and formation of naked singularities in selfsimilar gravitational collapse for an adiabatic perfect fluid. Conditions are obtained for the singularity to be either locally or globally naked and for the families of non-spacelike geodesies to terminate at the singularity in past. This is shown to be a strong curvature naked singularity in a powerful sense and an interesting relationship is pointed out between positivity of energy and occurrence of naked singularity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
97
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 10 publications
1
97
0
Order By: Relevance
“…Gravitational collapse has been extensively studied in modified gravity theory i.e., in Gauss-Bonnet, f (R) gravity, Lovelock theory etc [28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46]. Scheel [47] demonstrated that Openheimer-Snyder collapse in Brans-Dicke theory results in BHs rather than NSs with the positive values of brans-dicke parameter ω, they have speculated that the apparent horizon of a BH can pass outside the event horizon causing the decrease in the surface area over time.…”
Section: Introductionmentioning
confidence: 99%
“…Gravitational collapse has been extensively studied in modified gravity theory i.e., in Gauss-Bonnet, f (R) gravity, Lovelock theory etc [28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46]. Scheel [47] demonstrated that Openheimer-Snyder collapse in Brans-Dicke theory results in BHs rather than NSs with the positive values of brans-dicke parameter ω, they have speculated that the apparent horizon of a BH can pass outside the event horizon causing the decrease in the surface area over time.…”
Section: Introductionmentioning
confidence: 99%
“…The visibility is determined by the existence (or lack thereof) of outgoing null geodesics with past endpoint at the singularity. To investigate the existence of such geodesics, we use the general method originally developed by Joshi and Dwivedi [14]. One defines the quantity x = R/2m α (where 1/3 < α ≤ 1) and observes that, at the singularity, both R and m vanish.…”
Section: Spherical Collapse With Tangential Stressesmentioning
confidence: 99%
“…These studies show that the behaviour of the free functions describing the mass and velocity distributions of the particles in the cloud are the crucial elements that determine the final outcome of collapse (see for example [4]). Several studies aimed at clarifying the role of pressures in collapse models have also been done [5], with some models considering analytical solutions for collapse of perfect fluids with adiabatic equations of state [6], in order to determine the end states, resulting in a covered singularity or otherwise (see [7] and references therein). The key result that emerges from the many models studied over the years is that there are essentially two possible scenarios to describe relativistic gravitational collapse:…”
Section: Introductionmentioning
confidence: 99%